2019
DOI: 10.1016/j.scitotenv.2019.05.240
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy as a useful tool to predict land use depending on Mediterranean contrasted climate conditions: A case study on soils from olive-orchards and forests

Abstract: • FTIR-ATR was used to test land use effect on soil chemical properties. • Soil chemical signature differs between olive-tree orchards and Mediterranean forests. • Climate (Humid vs Sub humid, coastal vs inland area) also shapes soil properties. • PLS modeling confirmed that FTIR-ATR is a useful tool to predict land use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…This was achieved by using ANOVA Common Dimension (AComDim) method to prioritize the significant factors and their interactions from Fourier Transform Infrared (FTIR) signatures of MOL leaf samples, harvested over three years and in different agroclimatic zones of Cameroon. This multi-block method has shown its effectiveness in different fields [16][17][18][19] and is especially interesting because it uses all the spectral variance for each level of factors studied. In this study, five factors with different sub-levels were considered such as the collection year and month, the agroclimatic zone of harvest (defined according to Liénou et al [20], the soil nature (defined according to the classification of Segalen [21]) and the maturity of MOL leaves.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by using ANOVA Common Dimension (AComDim) method to prioritize the significant factors and their interactions from Fourier Transform Infrared (FTIR) signatures of MOL leaf samples, harvested over three years and in different agroclimatic zones of Cameroon. This multi-block method has shown its effectiveness in different fields [16][17][18][19] and is especially interesting because it uses all the spectral variance for each level of factors studied. In this study, five factors with different sub-levels were considered such as the collection year and month, the agroclimatic zone of harvest (defined according to Liénou et al [20], the soil nature (defined according to the classification of Segalen [21]) and the maturity of MOL leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings support the hypothesis that although vegetation overstory does influence SOC chemistry to some extent, other site factors and ecosystem interactions (e.g., microbial community, soil parent material and soil nutrient availability) modify and ultimately determine soil organic matter composition and stabilization (Cotrufo et al, 2013;Schmidt et al, 2011;Wickings et al, 2012). The influence of other factors such as landuse history (e.g., grazing, logging), fire regime and local climate variations was disregarded in this study, but can also influence SOC chemistry, as has been observed in forests and agroecosystems across different climatic areas (Delcourt et al, 2019;James et al, 2019).…”
Section: Influence Of Site Conditions On Soc Stabilization and Chemistrymentioning
confidence: 99%
“…Among the few studies related to the effect of land-use history on Mediterranean forest soils, it was shown that (i) quantitative changes in soil organic matter (lipids and humic acid fractions) between undisturbed Mediterranean forests and neighbouring deforested sites (Tinoco et al, 2010), (ii) vegetation thinning treatments, more frequent in Mediterranean forests, modified physical and microbiological properties in comparison with soil quality of unmanaged and undisturbed forest areas (Andrés-Abellán et al, 2019;Lull et al, 2020;Wic Baena et al, 2013), (iii) different land uses and agricultural practices were discriminated by the aromatic and carbonate compounds in the soils (Delcourt et al, 2019;Du et al, 2008;Mendham et al, 2002), (iv) soils keep, at different depths, the marks of past uses in their chemical composition and their spectral signature appears like an "historical footprint" of their natural or anthropogenic conversion over time (Ertlen et al, 2015;Vysloužilová et al, 2015), (v) different chemical signatures of forest soils were observed under different bioclimatic stages (Delcourt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Differences of soil physico-chemical properties due to agricultural activities can endure for many years even after use, but few studies have used spectral technique to follow recolonization by native vegetation of abandoned farmed sites, though spectroscopy was recognized to be a promising analytical method for investigating soil sciences (Tinti et al, 2015;Aranda et al, 2014). Spectroscopy was used to detect changes in soil quality, plant cover and to predict soil classification according to different land-use categories (Delcourt et al, 2019;Ertlen et al, 2015Ertlen et al, , 2010Paz-Kagan et al, 2014;Du and Zhou 2009).…”
Section: Introductionmentioning
confidence: 99%